Lower Limb Rehabilitation System Interfaced with a Videogame: A Potential Application for Landmine Victims - Yepes, J. C.; Franco, R.; Zuluaga, R.; Zaldarriaga, A. J.; Perez, V. Z.; Betancur, M. J. (Revista Mexicana de Ingenieria Biomedica, 2016)
Worldwide there are approximately 3,308 records of landmine victims during a year. 67% of them suffered injuries which require physical rehabilitation. This paper presents a data acquisition system for landmine victims rehabilitation, interfaced with a videogame, which enables to interact with a racing game. The therapist can set the minimum speed required for the rehabilitation and analyze the forces and speed developed while pedaling. The conceptual development incorporates a commercial static bicycle, sensors to measure the pedaling force, an optic sensor to measure the speed, and command buttons to control the videogame. In order to evaluate the system, the sensors were characterized and tested, and a survey was conducted to 20 physiotherapists in order to evaluate the perception of ergonomics, safety and possible benefits of the data acquisition system for rehabilitation of landmine victims. 70%, 90% and 80% of the physiotherapists, respectively, assessed these characteristics as High level. Moreover, at least 85% of them agrees with nine possible benefits for rehabilitation of landmine explosion victim. Therefore, it is proposed that the data acquisition system can be used as a serious game that supports rehabilitation therapies of people with a prosthesis due to this cause.